The Role of Blockchain Technologies in Changing the Structure of the Financial and Credit System - BIRIUK, Dmytro; YATSENKO, Oleksandr; KREKOTEN, Iryna; ROSSIKHINA, Halyna; CHYCHKALO-KONDRATSKA, Iryna (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
Purpose of the article is to determine the correlation and influence between the indicators of the development of blockchain-based technologies and the indicators of financial inclusion in countries with different levels of development. The research employed statistical methods, descriptive method, correlation analysis, and regression analysis. The constant transformation of the financial and credit system in the conditions of the rapid development of technologies requires finding ways to adapt to changes. Assessing the impact of blockchain on the development of the financial and credit system allows you to prepare for such changes and use them to your advantage. As a result of the conducted research, it was determined that by 2027 the blockchain market will grow 166 times (compared to 2017). The conducted analysis made it possible to establish that the main advantage of blockchain is to increase financial inclusion to improve access to at least basic financial services for users. It has been confirmed that the lower the level of financial inclusion in the country, the greater the share of the population turns to alternative options for access to credit funds using blockchain-based cryptocurrencies. In particular, it was found that more than 19% of the variation in the indicator of the share of cryptocurrency owners can be explained by the change in the percentage of the population without access to banking services. It was confirmed that the lower the level of financial inclusion in the country, the greater the share of the population turns to alternative options for access to credit funds using blockchain-based cryptocurrencies. It was also found that more than 19% of the variation in the indicator of the share of cryptocurrency owners can be explained by the change in the percentage of the unbanked population. What is new in the research is the formation of its own approach to assessing the impact of blockchain technology on financial inclusion in countries with different levels of development.